DIGITAL TRANSFORMATION OF LOGISTICS MANAGEMENT THROUGH A WEB-BASED BARCODE-INTEGRATED SHIPMENT INFORMATION SYSTEM - Nadila Muliana; Edy Rahman Syahputra (Ninety Media Publisher, 2026)
This study aims to design and implement a web-based shipment information system integrated with barcode technology to improve the efficiency and accuracy of goods delivery management at PT. Anugerah Fajar. The existing shipment management process relied heavily on manual recording methods, which resulted in data entry errors, delays in updating shipment status, and limited visibility of goods in transit. To address these issues, a barcode-based information system was developed to automate shipment identification, tracking, and reporting processes. The system was developed using the Rapid Application Development (RAD) methodology, which emphasizes iterative development and active user involvement. Data were collected through direct observation, interviews with administrative and field personnel, documentation analysis, and literature review. The proposed system includes core features such as user authentication, shipment data management, barcode scanning using one-dimensional (1D) barcodes, real-time shipment status updates, report generation, and system configuration. The results show that the implemented system successfully improves operational efficiency by reducing manual data entry and minimizing human errors in shipment recording. Real-time barcode scanning enables faster and more accurate shipment status updates, enhancing transparency and control throughout the distribution process. Additionally, the dashboard and reporting features support effective monitoring, documentation, and managerial decision-making. The findings indicate that integrating barcode technology into a web-based shipment information system provides a practical and scalable solution for modern logistics management. This research contributes to the field of information systems by demonstrating the effectiveness of barcode-based digital solutions in improving logistics operations within distribution companies.